Soul as Explanatory Cause of Life in Aristotle: Scientific Knowledge simpliciter (ἁπλῶς) through Coextensive Universal Demonstrations and Context Restriction as a Solution to a Core-Dependent Homonymy from APo 2.17 and de An. 2.1-4 - Farhat, Ahmad Suhail (Revista Archai, 2025)
The main purpose of this paper is to show, based on Aristotle’s theory of scientific demonstration, how soul plays the role of explanatory cause of life in De Anima (henceforth de An.) 2.1-4. Firstly, I evaluate Aristotle’s requirement, in Posterior Analytics (henceforth APo) 1.2 and 2.16, that universal demonstrations must satisfy a coextensional criterion between a given explanandum (A-term) and its most appropriate explanans (B-term). In addition, I argue that this criterion does not entail a causal symmetry between both those terms. Following Angioni (<a href="https://www.scielo.br/j/archai/a/c3nPF3kFy7r6ZMgMDQqsMZh/?lang=en#B5_ref" data-ref="ANGIONI, L. (2014a). Aristotle on Necessary Principles and on Explaining X Through the Essence of X. Studia Philosophica Estonica 7, n. 2, p. 88-112.">2014a) and Zuppolini (2018), I argue that, whenever one is before apparent multiple-causes scenario cases(in which there seems to be more than one possible cause to the same explanandum(, one shall still find a unified and fully appropriate explanation of that explanandum. In the second part of this paper, I examine an example from de An. 2.1-4 in view of APo 2.16-17. I argue that soul might be pointed out as the explanatory principle (B) that explains why life (A) belongs to a living body (C). Also, I argue that, although there is a core-dependent homonymy taking place between plants (γ1), animals (γ2) and the nutritive capacity (α1), the nutritive soul (β1) plays the role of an incidental factor (συμβεβηκός) in the context of a scientific demonstration that has by explananda whatsoever attributes (αn) that belong to animals (γ2) qua living beings endowed with a perceptive soul (β1) that explains why attributes (αn) belong to them.